Current understanding on TREM-2 molecular biology and physiopathological functions - Bharadwaj, Shiv; Groza, Yaroslava; Mierzwicka, Joanna M; Malý, Petr (International immunopharmacology, 2024)
Triggering receptor expressed on myeloid cells 2 (TREM-2), a glycosylated receptor belonging to the immunoglobin superfamily and especially expressed in the myeloid cell lineage, is frequently explained as a reminiscent receptor for both adaptive and innate immunity regulation. TREM-2 is also acknowledged to influence NK cell differentiation via the PI3K and PLCγ signaling pathways, as well as the partial activation or direct inhibition of T cells. Additionally, TREM-2 overexpression is substantially linked to cell-specific functions, such as enhanced phagocytosis, reduced toll-like receptor (TLR)-mediated inflammatory cytokine production, increased transcription of anti-inflammatory cytokines, and reshaped T cell function. Whereas TREM-2-deficient cells exhibit diminished phagocytic function and enhanced proinflammatory cytokines production, proceeding to inflammatory injuries and an immunosuppressive environment for disease progression. Despite the growing literature supporting TREM-2+ cells in various diseases, such as neurodegenerative disorders and cancer, substantial facets of TREM-2-mediated signaling remain inadequately understood relevant to pathophysiology conditions. In this direction, herein, we have summarized the current knowledge on TREM-2 biology and cell-specific TREM-2 expression, particularly in the modulation of pivotal TREM-2-dependent functions under physiopathological conditions. Furthermore, molecular regulation and generic biological relevance of TREM-2 are also discussed, which might provide an alternative approach for preventing or reducing TREM-2-associated deformities. At last, we discussed the TREM-2 function in supporting an immunosuppressive cancer environment and as a potential drug target for cancer immunotherapy. Hence, summarized knowledge of TREM-2 might provide a window to overcome challenges in clinically effective therapies for TREM-2-induced diseases in humans.
Keywords: Cancer; signální transdukce; Signal Transduction; Immunity, Innate; Receptors, Immunologic; Humans; T-Lymphocytes; receptory imunologické; Inflammation; lidé; Immunotherapy; zvířata; buňky NK; membránové glykoproteiny; Membrane Glycoproteins; Killer Cells, Natural; Phagocytosis; fagocytóza; Neoplasms; Cytokines; nádory; T-lymfocyty; Animals; přirozená imunita; Cell signaling